PENGARUH SUMBER DAYA MANUSIA DALAM KEMAJUAN PERUSAHAAN KFC - Bagas Sabirin; Hendra Riofita (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2024)
KFC(Kentucky Fried Chicken) is one of the fast food restaurants originating from the United States that has gone global, every country has one of these restaurants in each of their regions whose main ingredient is chicken fried using their company's secret spices. This study uses a descriptive qualitative method whose data collection uses previous journals. And also the purpose of making this journal is to find out about the influence of HR on the progress of the KFC company starting from analysis, marketing strategy, recruitment, training, and work culture in the company. The results of data collection show that KFC does its employees well based on their quality, especially for new employees who get intense training so that in their service customers are satisfied and do not forget that KFC maintains the quality of their food and the taste of their food for the satisfaction of their customers.